Analyzing the Integration of Computational Thinking in Science and Physics Education within the Indonesian Curriculum - Irvani, Asep Irvan; Rochintaniawati, Diana; Riandi, Riandi; Sinaga, Parlindungan (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2024)
This field study was carried out to reveal the implementation of computational thinking in learning Natural Sciences and Physics in the Independent Curriculum. The study was conducted in Garut Regency targeting science, physics and ICT teachers in schools that have implemented the Independent Curriculum. The number of respondents involved was 112 teachers who were selected using the cluster sampling method. Respondents consisted of 57.1% elementary school teachers, 31.3% middle school teachers, and 11.6% high school/equivalent teachers. The instruments used include questionnaires, observation sheets, and document analysis sheets. Data analysis was carried out using triangulation techniques from research data. The research results show that conceptually teachers still do not understand computational thinking. Even though some teachers are aware of the emphasis on implementing computational thinking in the independent curriculum, the documents for planning and implementing learning in the classroom still do not show this implementation. These results can be used as a basis for conducting training and assistance to science and physics teachers in implementing computational thinking in learning.